The Effects of High School Peers' Gender on College Major, College Performance and Income - Massimo Anelli; Giovanni Peri (Center for Economic Studies and ifo Institute (CESifo), 2016)
Using an originally constructed dataset that follows 30,000 Italian individuals from high school to the labor market, we analyze whether the gender composition of peers in high school affected their choice of college major, their academic performance and their labor market income. We exploit the within-school, cohort-by-cohort variation in the gender composition of high school classmates (peers), after controlling for school and teachers fixed effects. We find that male students graduating from classes with a large majority of male peers were more likely to choose “prevalently male” (PM) college majors (Economics, Business and Engineering). However, this impact was partially undone during college through attrition, worse academic performance and change in major. And in the long run it did not produce any difference in income or labor market outcomes. We do not find significant effects of the high school class gender composition on women. Our results are consistent with the fact that individuals are affected by the choice/pressure of the network of friends and with the observation that network size responds to class gender composition more for men than for women.
Keywords: I21; J16; J24; J31; Z13; 330; peer effects; high school; gender; networks; choice of college major; academic performance; wages